TRILINGUAL TEXTUALIZATION TO DELIVER INDONESIAN LOCAL CULTURES TO HIGH SCHOOL STUDENTS - Sunarto, Emmanuel; Mukarto, F. X.; Bismoko, J.; Dewi, Novita (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2018)
This article addresses issues surrounding translation of local texts from regional languages and cultures throughout the Indonesian archipelago into Indonesian and English. The textualization of the local culture to be documented includes: (1) folklore, (2) life-cycle rituals, (3) socio-religious rituals, (4) traditional medicine and other local wisdom, and (5) local culinary. It will discuss the formulation of the basic philosophy, themes, and values in the local texts to translate as well as principles of translation to apply. The study shows that textualization of the local texts helps support the politics of the national language, namely the use of Indonesian as the national language, the preservation of local languages as the fundamental support of the national culture, and the exposure of various local wisdoms to the global community. The availability of trilingual cultural texts will likely contribute to the promotion of human dignity.